PERSONALIZED APPROACH TO THE ASSESSMENT OF THE ANDROGENIC STATUS OF MEN WITH RAMEX - P. V. Glybochko; Y. G. Alyaev; M. E. Chaly; O. A. Usachyova (Сеченовский вестник)
The article under consideration deals with the problems of personalized approach to the assessment of the androgenic status of men with ramex.